Thrips in upland rice: preliminary investigation - Ferreira, Evane; Fernandes, Paulo Marçal (Pesquisa Agropecuaria Brasileira, 2014)
Thrips survey was conducted in the experimental fields of upland rice (Oryza sativa L.) located at Centro Nacional de Pesquisa de Arroz e Feijão (CNPAF/EMBRAPA). The results showed that Frankliniella rodeos (Thysanoptera - Thripidae) represented more than 90% of the insect population and was positively correlated with the number of sterile spikelets. The net sweeps yielded 10% of insect population present in the plants. Among the 23 rice entries tested for number of F. rodeos in the panicles, IR 9209-181-2 was significantly less infested as compared to the check cv. IAC-47.